2021
DOI: 10.3390/microorganisms9010141
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Broadly-Resistant to Last Resort Antibiotics Detected in Commercial Chicken Farms

Abstract: Resistance to last resort antibiotics in bacteria is an emerging threat to human and animal health. It is important to identify the source of these antimicrobial resistant (AMR) bacteria that are resistant to clinically important antibiotics and evaluate their potential transfer among bacteria. The objectives of this study were to (i) detect bacteria resistant to colistin, carbapenems, and β-lactams in commercial poultry farms, (ii) characterize phylogenetic and virulence markers of E. coli isolates to potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…AMR E. coli are commonly found in food producing animals such as in the gastrointestinal tract of chickens and facilities in which these chickens are housed [ 17 , 18 , 19 ]. The presence and persistence of resistance in commensal E. coli is a significant biomarker for the selective pressure enforced by antibiotic use and subsequent resistance predicted in other potentially pathogenic bacteria [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMR E. coli are commonly found in food producing animals such as in the gastrointestinal tract of chickens and facilities in which these chickens are housed [ 17 , 18 , 19 ]. The presence and persistence of resistance in commensal E. coli is a significant biomarker for the selective pressure enforced by antibiotic use and subsequent resistance predicted in other potentially pathogenic bacteria [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PCR-based methods have been widely accepted as gold standard for confirmation of resistance and are rapid, robust and reliable in detecting most resistant bacteria including carbapenemases [ 27 ]. A recent study by Jochum et al [ 28 ] reported a wide-spread abundance of carbapenem resistant E. coli (CRE) in commercial chicken farms in USA. The same study also reported the presence of extraintestinal pathogenic E. coli phylogenetic groups B2 and D from the chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Next, PCoA analysis indicated signi cant differences in the structures of ARGs among the six breeds of broilers. We speculated the composition of ARG types would be different because of the distinct microbial community structure and diversity of both feces and the internal environment of the chicken gut [36], or different feeding patterns in the different breeds of broiler [37]. In summary, the results showed that the gut of commercial broilers contained drug-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%